2011
DOI: 10.4103/1119-3077.79235
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dermatophytosis among primary school children in Oke-oyi community of Kwara state

Abstract: This study demonstrates that the prevalence of dermatophytoses in the school studied was significant. Control efforts should target this vulnerable group to reduce its prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
76
6
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(104 citation statements)
references
References 19 publications
15
76
6
3
Order By: Relevance
“…1,13,22,23,25 Similar to other studies, the majority of the tinea capitis cases were among boys below 15 years of age. 22,24,[45][46][47] Mahé et al's 37 study also revealed a lower proportion of tinea capitis (11%), but found higher prevalence rates of pyoderma (37%), contact dermatitis (18%), scabies (13%), and superficial mycosis (13%) compared to our findings.…”
contrasting
confidence: 53%
“…1,13,22,23,25 Similar to other studies, the majority of the tinea capitis cases were among boys below 15 years of age. 22,24,[45][46][47] Mahé et al's 37 study also revealed a lower proportion of tinea capitis (11%), but found higher prevalence rates of pyoderma (37%), contact dermatitis (18%), scabies (13%), and superficial mycosis (13%) compared to our findings.…”
contrasting
confidence: 53%
“…While the current study and that of Ofovwe and Ofili involved both public and private schools, that by Alex-Hart and Akani, was conducted among public schools only, suggesting a wide dichotomy between the private and public schools regarding the availability of toilet facilities in Nigeria. The preference for pit latrine as the means of sewage disposal in this study is in tandem with findings by other authors [1,4,5,24,25] and may be attributable to its ease of use by school pupils and minimal water requirements given the relative scarcity of water in the schools. When toilet facilities are inadequate in schools, pupils can engage in indiscriminate disposal of sewage materials which may result in outbreak of poor sanitary related diseases in the school community as was reported across the country recently [26].…”
Section: Healthful Livingsupporting
confidence: 77%
“…The incidence of dermatophytosis cases among elementary school students in Jatinangor was relatively low compared to studies conducted by various researchers, such as a study by Adefemi et al 16 in Kwara State, Nigeria discovered that the prevalence was about 5% (30/602). In addition, Komba and Mgonda 8 in Dar es Salaam, Tanzania, stated that the prevalence was 11.4 % (48/420).…”
Section: Discussionmentioning
confidence: 73%